Designing a MOOC Course in Teaching Fashion Design – A Case Study of Course Decorative Composition - Nguyen, Xuân Trà (Journal of Technical Education Science, 2023)
A Massive Open Online Course (MOOC), which is considered as a web-based distance online training program designed for a large number of geographically dispersed learners, is now becoming one of the contemporary trends in online education. The article presents the concept, characteristics, main components of a MOOC course and introduces the Gagne process applied for designing a MOOC course in connection with the specific analysis of teaching Fashion Design. The article also presents an illustration of the design of the MOOC course of the Decorative Composition subject in the Fashion Design industry with a typical selection of the topic "Silhouettes in fashion design" using of the Gagnes process. Sharing some valuable experiences for reference in the field of pedagogy, which still has many gaps, it is benificial to have other studies to further promote the application of digital pedagogy in training.